Inovasi Olahan Pangan Lokal sebagai Pemberian Makanan Tambahan pada Balita Stunting di Desa Sumput - Budi Prabowo; Hanif Firmansyah; Lini Pramesti Putri; Moch. Syahrul Firmansyah; Nisrina Dyah Ayu Nurani (Institut Nalanda, 2024)
The problem of growing growth in toddlers that still occurs in Indonesia is stunting, which is a condition of lack of nutrition for a long time so that resulting in the impediments of the height of the child and not in accordance with his age. One way that can be used to address stunting problems is with Supplemental Food Providing (PMT) aimed at helping nutrition improvement through food selection and eating habits in toddlers. Based on national prevalence figures, the largest percentage of stunting problems comes from East Java Province, precisely in Sidoarjo Regency. Therefore, students of KKN-T Bela Negara UPN “Veteran” East Java group 06 waves 1 held a Free Stunting Socialization activity (SIBUNTING) in Sumput, Sidoarjo. This activity is done by providing education about the dangers of stunting in children and providing extension around the creation of the Supplementary Food Providing menu (PMT) aimed at adding knowledge and accelerating changes in the behavior of mother and toddler families in the Sumput village in feeding habits in children.